2018
DOI: 10.1007/s40262-018-0704-z
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of the Interleukin-23 Inhibitor Risankizumab in Subjects with Psoriasis and Crohn’s Disease: Analyses of Phase I and II Trials

Abstract: Background and Objectives Risankizumab is a humanized anti-interleukin-23 monoclonal antibody in development for the treatment of several inflammatory diseases. This work characterized the pharmacokinetics of risankizumab and evaluated covariates that may affect its exposures using phase I and II trial data in subjects with psoriasis and Crohn's disease. Methods Plasma concentration measurements from a phase I study and a phase II study in subjects with psoriasis (n = 157; single doses of 0.01-5 mg/kg intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…ADA titers in the patients who were ADA positive ranged from one to 16; these low-titer ADAs did not affect risankizumab exposure based on the comparable risankizumab trough concentrations in ADA-positive and ADA-negative subjects in the study (data not shown). These results are consistent with the population pharmacokinetic analysis of risankizumab conducted using data from phase I and II studies in patients with psoriasis and Crohn's disease [13].…”
Section: Pharmacokineticssupporting
confidence: 85%
See 2 more Smart Citations
“…ADA titers in the patients who were ADA positive ranged from one to 16; these low-titer ADAs did not affect risankizumab exposure based on the comparable risankizumab trough concentrations in ADA-positive and ADA-negative subjects in the study (data not shown). These results are consistent with the population pharmacokinetic analysis of risankizumab conducted using data from phase I and II studies in patients with psoriasis and Crohn's disease [13].…”
Section: Pharmacokineticssupporting
confidence: 85%
“…Blood samples for determination of risankizumab plasma concentrations and detection of risankizumab anti-drug antibody (ADA) were collected just prior to risankizumab dosing on days 8, 36, 64, 92, 105, and 204; an additional blood sample for risankizumab plasma concentrations was collected on day 98. Risankizumab plasma concentrations and ADA were measured as previously described [5,13]. Briefly, risankizumab plasma concentrations were determined using a validated, enzyme-linked immunosorbent assay method in which a polyclonal anti-risankizumab antibody was used as the capture reagent and a biotinylated anti-idiotypic risankizumab antibody was used as the detection reagent.…”
Section: Pharmacokinetic Sampling and Bioanalytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An approximately dose proportional increase in risankizumab exposure was observed following repeated administration of 90 and 180 mg subcutaneous doses in the global phase II study [17,23], and between 75 and 150 mg subcutaneous doses in the Japanese phase II/III studies [13].…”
Section: Multiple-dose Pharmacokineticsmentioning
confidence: 92%
“…In psoriasis patients with inactive IBD, we recommend that the TNF antagonists: adalimumab, certolizumab pegol and infliximab; the IL12/23 inhibitor: ustekinumab; the IL23/p19 inhibitors: guselkumab, risankizumab and tildrakizumab; as well as the synthetic drug apremilast, and the conventional drugs, methotrexate, cyclosporine, fumarates and acitretin, can all be used as systemic treatments as they also have a beneficial or neutral effect on IBD symptoms. [15][16][17] We advise caution with use of the following anti-IL17 biological drugs: secukinumab, ixekizumab and brodalumab, to treat psoriasis patients with inactive IBD, and in those patients with a family history of IBD. 6 We also advise not using etanercept in these patients due to the possibility of a flare-up of IBD symptoms.…”
Section: Clinical Recommendationsmentioning
confidence: 99%